Evaluation of Role of Prognostic Factors on Hearing Outcome in Unilateral Idiopathic Sudden Onset Sensorineural Hearing Loss - Namrata Yadav; Priti Lal; Rohit Bharadwaj; Kuldeep Yadav (Bengal Journal of Otolaryngology and Head Neck Surgery)
Introduction: Owing to its uncertain and multiple possible etiologies, use of multiple empirical treatment regimens and possibility of spontaneous recovery, it becomes important to look for the possible prognostic factors affecting the outcome of sudden sensorineural hearing loss (SSNHL).